The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1525-1314.2009.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐induced incipient amorphization of α‐quartz and transition to coesite in an eclogite from Antarctica: a first record and some consequences

Abstract: Monocrystalline quartz inclusions in garnet and omphacite from various eclogite samples from the Lanterman Range (Northern Victoria Land, Antarctica) have been investigated by cathodoluminescence (CL), Raman spectroscopy and imaging, and in situ X-ray (XR) microdiffraction using the synchrotron. A few inclusions, with a clear-to-opalescent lustre, show ÔanomalousÕ Raman spectra characterized by weak a-quartz modes, the broadening of the main a-quartz peak at 465 cm )1 , and additional vibrations at 480-485, 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 118 publications
2
13
0
Order By: Relevance
“…However, the Raman spectrum of coesite is normally characterised by additional peaks at 204, 270, 355 and 426 cm −1 , which were not present in our sample . A similar situation was previously noted in the quartz spectrum in an eclogite from Antartica . In the latter case, it was proposed that the coesite crystalline structure was attained at the nanometric scale within anomalous α ‐quartz (called cryptic coesite), which developed under high pressure.…”
Section: Discussionsupporting
confidence: 82%
“…However, the Raman spectrum of coesite is normally characterised by additional peaks at 204, 270, 355 and 426 cm −1 , which were not present in our sample . A similar situation was previously noted in the quartz spectrum in an eclogite from Antartica . In the latter case, it was proposed that the coesite crystalline structure was attained at the nanometric scale within anomalous α ‐quartz (called cryptic coesite), which developed under high pressure.…”
Section: Discussionsupporting
confidence: 82%
“…The two possible directions of tetrahedral tilt are equally likely, and they give rise to two distinct twin orientations, commonly denoted as Dauphin twins [37]. It was previously proposed that the widening of A 1 Raman mode is due to the appearance non-visible E Raman mode [38]. But in Figure 5a it is observed that the intensity for E Raman modes remains constant and the intensity of the signal at 468 cm -1 varies.…”
Section: Resultsmentioning
confidence: 96%
“…The Raman band of 520–523 cm −1 corresponds to the four‐membered rings of a corner‐sharing SiO 4 tetrahedron of the coesite (Kingma & Hemley, ). The incipient APSI phase characteristically shows high intensity ratios I 265 / I 465 and I 402 / I 465 , where I ν indicates the intensity of the Raman band ν (Godard, Frezzotti, Palmeri, & Smith, ; Palmeri et al., ). In contrast to the incipient APSI phase, the APSI phase of the Yangzhuang sample described in this study does not show any Raman bands assigned to those of α‐quartz and coesite (spots 1–2 in Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The weak band at 602 cm −1 can be assigned to the symmetric stretching vibration of Si‐O in a planar three‐membered SiO 4 ring (D 2 band) of amorphous SiO 2 glass (Awazu & Kawazoe, ; Ivanda et al., ). Raman spectra, TEM observation, and SAED analysis (Figure d,e) suggest that the APSI phase in the sample is almost entirely in an amorphous state, unlike the incipient APSI phase reported from the Antarctica (Palmeri et al., ) and the western Alps (Frezzotti et al., ) samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation